The Mediating Role of Self-Alienation between Fear of Covid-19 and Smartphone Addiction - Halil İbrahim ÖZOK; Gamze Mukba; Volkan Tayiz (Foxton Books, 2022)
The Covid-19 pandemic, which affects all areas of life, also continues to affect addiction situations. The present study was conducted to investigate the relationships among self-alienation, fear of Covid-19 and smartphone addiction. Within the scope of the research, 4 hypotheses were tested. Using the "Structural Equation Model" (SEM), the mediating role of "Self-alienation" between "Fear of Covid-19" and "Smartphone Addiction" was examined. This study included 619 university students who were enrolled in the 2021-2022 academic year. These students of 429 (69.3%) are female and 190 (30.7%) are male. Participants are studying via distance education. Data were obtained with "Personal Information Form", "Fear of Covid-19 Scale", "Alienation Scale" and "Smartphone Addiction Scale". As a result of the research, all of the hypotheses have been proven. In addition, it has been found that university students scored high levels on "Fear of Covid-19", "Self-alienation" and "Smartphone Addiction".